Keefektifan Learning Management System (LMS) Berbasis Moodle Menggunakan Model Delone And Mclean - Vivi Fiyola; Nur Nawaningtyas Pusparini (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
Binawan University, situated in East Jakarta, faced the repercussions of the COVID-19 outbreak, leading to the adoption of online learning through a Learning Management System (LMS) based on Moodle. The university has been utilizing the LMS since 2019. However, challenges arise in the Nutrition study program, where the effectiveness of the LMS and seamless communication between the Academic information systems and LMS remain imperfect. To assess the LMS's effectiveness, the research employs the Delone And Mclean method. The study aims to evaluate the efficacy of the Moodle-based LMS in the Nutrition program at Binawan University and assess the integration between the academic information system and the LMS. Findings from the research indicate that, according to the Delone And Mclean method, the overall quality of the LMS in the nutrition study program at Binawan University is good, achieving a score of 69.36% in system testing.